Exploring space [compact disc]. - Palca, Joe (American chronicles (National Public Radio (U.S.)), 2013)
From the competitive spirit ignited by Sputnik to the tragedies and triumphs of the Apollo missions, from the technological leap forward created by the Space Shuttle to the global cooperation forged by the International Space Station and beyond, NPR examines the inspirational story of modern space exploration and the extraordinary individuals who made it possible.